Evaluation of the utricular and saccular function using oVEMPs and cVEMPs in BPPV patients - Xu, Hui (J Otolaryngol Head Neck Surg, 2016)
BACKGROUND: It is well-known that ocular vestibular evoked myogenic potentials (oVEMPs) predominantly reflect utricular function whilst cervical vestibular evoked myogenic potentials (cVEMPs) reflect saccular function. To date, there are no published reports on the systemic evaluation of utricular and saccular function in benign paroxysmal positional vertigo (BPPV), nor are there any reports on the differences in VEMPs between patients with recurrent and non-recurrent BPPV. The aim of this study was to evaluate the difference in cervical and ocular (c/o)VEMPs between patients with BPPV and normal controls, as well as between patients with recurrent and non-recurrent BPPV. METHODS: Thirty patients with posterior canal BPPV and 30 healthy subjects (as normal controls) were prospectively enrolled. cVEMP and oVEMP testing using 500 Hz tone-burst stimuli were performed on all. VEMP tests were repeated 3 times on each subject to ensure reliability and reproducibility of responses. VEMPs were defined as present or absent. Abnormal VEMP was defined by lack of VEMP response. RESULTS: In the control group, abnormal cVEMPs responses were detected in 6.67 % and abnormal oVEMPs responses were detected in 3.34 %. In BPPV patients (10 with recurrent BPPV, 20 with non-recurrent BPPV), abnormal cVEMPs responses were detected in 30 % and abnormal oVEMPs responses were detected in 56.7 %. More patients with BPPV showed abnormal responses in c/oVEMPs as compared to the control group (p < 0.05). oVEMPs was more often abnormal as compared to cVEMPs in BPPV patients (p < 0.05). There was no statistical difference between abnormal cVEMP responses in non-recurrent BPPV patients (25 %) and recurrent BPPV patients (40 %) (p > 0.05). Differences in abnormal oVEMP responses (non-recurrent BPPV, 40 %; recurrent BPPV, 90 %) were significant (p < 0.05). CONCLUSION: An increased occurrence of abnormal c/oVEMP recordings appeared in BPPV patients, possibly as a result of degeneration of the otolith macula. oVEMPs were more often abnormal in BPPV patients as compared to cVEMPs, suggesting that utricular dysfunction may be more common than saccular dysfunction. Furthermore, oVEMP abnormalities in the recurrent BPPV group were significantly higher than those in the non-recurrent BPPV group. Assessment of c/oVEMPs in BPPV patients may therefore be of prognostic value in predicting likelihood of BPPV recurrence.